Visual Strategies in Video Branding to Build a Professional Image: A Case Study of the Video “Pruways” - Firdaus Tara Putra; Pratama Bayu Widagdo (Gorga : Jurnal Seni Rupa, 2025)
In a competitive digital era, video has become an important strategy in brand communication to build a professional image. This study analyzes the internal video "PruWays" produced by Prudential Syariah Indonesia with a descriptive qualitative approach to explore how visual elements such as framing, color, lighting, and brand symbols are designed to shape perceptions of professionalism. The key issue was how to communicate sharia values aesthetically and strategically to foster employee ownership. Analysis showed that framing techniques such as rule of thirds and center framing succeeded in building a sense of professionalism, order, and visual authority. The use of a red and teal green color palette incorporates a sense of boldness and spirituality that reinforces the corporate identity. Soft lighting and natural daylight create an inclusive and friendly atmosphere, while visual symbols such as logos, collaborative gestures, and modern layouts reinforce sharia values such as ukhuwah, amanah, and ihsan. The tangible impact is evident from the increased employee participation in post-screening discussion forums, which shows emotional engagement has translated into collective action. This research aims to identify and explain how visual elements in internal videos can be used strategically to shape a professional image and communicate organizational values to employees. The limitations of this research lie in the single object focus and the non-use of quantitative perception measures, so the results are exploratory and require further study for wider validation.